Synthesis of Ag-Pt alloy nanoparticles in aqueous bovine serum albumin foam and their cytocompatibility against human gingival fibroblasts - Singh, A. V.; Patil, R.; Kasture, M. B.; Gade, Wasudeo N.; Bhagavatula L. V. Prasad (Colloids and Surfaces B-Biointerfaces, 2009)
Foams of bovine serum albumin (BSA) have been utilized for synthesizing in situ protein capped Ag-Pt alloy nanoparticles. The in vitro cytotoxicity and the rate of proliferation of human gingival fibroblasts (HGFs) in presence of the above synthesized alloy nanoparticles is investigated. Expression profile of protein involved in detoxification, i.e. metallotheonein (MT) were assayed by ELISA and expression of mRNA transcripts by reverse transcription polymerase chain reaction (RT-PCR). Cytotoxicity results suggested that protein capped nano-alloys might be promising candidates for implants and prosthetic material. RT-PCR and ELISA confirmed the expression of MT. in cells treated with the alloy nanoparticles. Morphology variation studied by SEM also confirms that cells treated with alloy nanoparticles present an intact morphology. (C) 2008 Elsevier B.V. All rights reserved.
Keywords: Alloy nanoparticles; Biocompatibility; ELISA; Human gingival fibroblasts; mRNA; Protein foams